Incidencia de la facturación electrónica en la rentabilidad de las imprentas autorizadas por el servicio de rentas internas (sri) en el Cantón Latacunga en el período 2016 -2017 - Cóndor Llumiquinga, Jimena Alexandra (2018)
The investigation project entitled The incidence of Electronic Billing in the Profitability of printing shops authorized by the Internal Revenue Service during the 2016-2017 period in Latacunga, focuses on analyzing the effect that brings with the adoption of electronic billing in the profitability of the authorized printing shop for which it is taken as the object of study, Gutenberg and Andina print shops are obligated to run accounting, and for the development of this project it was necessary to build a theoretical basis based on independent and dependent variables, starting from a descriptive, explanatory and analytical research, with methodological documentary and field approach, which will use interview and analysis of financial indicators as an analysis instruments, that’s why it is taken as a reference the indicator of net profit margin which indicates that in 2017 Gutenberg print shop reflects 6,29 %, while in 2016 is evidenced a decrease to 4,16% , in similar way Andina from 21,99% in 2017 to 6,40% in 2016, therefore it reaches the interpretation and analysis that proved the general hypothesis. The main conclusion of this research is that there is an impact on the profitability of authorized printing shops because they were affected by the implementation of electronic billing; when replacing physical documents with electronic ones, the printing of the different legal documents was suspended, affecting to the economy of the same ones, contrasting that the owners mention in interviews do not have any effect by this new process.